Epidemiological Features of Lumbar Disc Lesion in Patients Reporting Neurosurgery at DHQ Mirpur (Medical Forum Monthly, 2024)
Objective: This study examined the social and demographic characteristics of lumbar disc prolapse in patients reporting to outpatients department of Neurosurgery at DHQ Hospital Mirpur AJKStudy Design: Observation / descriptive studyPlace and Duration of Study: This study was conducted at the Department of Neurosurgery, DHQ hospital Mirpur from June 2015 to January 2017Materials and Methods: A total of 108 patients with proven lumbar disc prolapse on MRI who attended the neurosurgical outpatient from June 2015 to January 2017 were included in the study.Results: The most common age group involved was between 31-40 years and 41-50 years (31.5 % each). The most commonly affected level was L4/5 (44.4 %). Majority of patients affected (66.7%) were from rural areas. 44.4 % were moderate and 29.6% were heavy workers. The patients who drove vehicle on bad roads were more affected.Conclusion: Lumbar disc prolapse is common in people working or living in poor infrastructure